Blood Profile and Leukocyte Differentiation of Coturnix coturnix japonica with Addition of African Leaf Juice (V. amygdalina) in Drinking Water (Jurnal Sain Peternakan Indonesia, 2024)
This study aimed to assess the impact of incorporating African leaf juice into drinking water on the blood profile. A completely randomized design was used with 120 laying quail divided into three treatments and five replicates. The treatments included a control group (without African leaf juice) and two groups with African leaf juice added to their drinking water at 3 ml/bird/day doses and 6 ml/bird/day. The results showed that adding African leaf juice 3 ml and 6 ml/bird/day in drinking water decreased haemoglobin. Adding 3 and 6 ml/bird/day of African leaf juice in drinking water did not affect leukocyte differentiation. It was concluded that adding 3 ml/bird/day of African leaf juice could be used in quail drinking water.